Efektivitas Penggunaan Kereta Listrik (KRL) Commuter Line Jabodetabek Untuk Mengurangi Kemacetan Di DKI Jakarta - Siti Sahara; Bayu Nurcahyo Adhi Nugroho (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The KRL Commuter Line is an alternative transportation facility emphasized by the government to address congestion issues in the Jabodetabek area. The primary focus of this research is on the utilization of the KRL Commuter Line by Jabodetabek commuters, who make up the largest group of commuters in Jakarta. This research is concentrated on the analysis of the KRL Commuter Line's public transportation in Jabodetabek with the main objective of assessing its effectiveness in addressing congestion problems in Jakarta. The method used is a qualitative approach with descriptive analysis, and data is obtained through literature research. The research results indicate that the utilization of the KRL Commuter Line in Jabodetabek to address congestion in Jakarta is considered successful, assessed through three main dimensions: goal achievement, integration, and adaptation.